2017
DOI: 10.1158/1078-0432.ccr-17-0803
|View full text |Cite
|
Sign up to set email alerts
|

Combined CDK4/6 and mTOR Inhibition Is Synergistic against Glioblastoma via Multiple Mechanisms

Abstract: Purpose Glioblastoma (GBM) is a deadly brain tumor marked by dysregulated signaling and aberrant cell cycle control. Molecular analyses have identified that the CDK4/6-Rb-E2F axis is dysregulated in about 80% of GBMs. Single-agent CDK4/6 inhibitors have failed to provide durable responses in GBM, suggesting a need to combine them with other agents. We investigate the efficacy of the combination of CDK4/6 inhibition and mTOR inhibition against GBM. Experimental Design Preclinical in vitro and in vivo assays u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 47 publications
(56 reference statements)
2
72
0
Order By: Relevance
“…These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72]. It is important to try to reconcile these observations with those previously observed that report CDK1 as the principal kinase that phosphorylates 4E-BP1 during mitosis [30,33].…”
Section: Discussionmentioning
confidence: 77%
“…These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72]. It is important to try to reconcile these observations with those previously observed that report CDK1 as the principal kinase that phosphorylates 4E-BP1 during mitosis [30,33].…”
Section: Discussionmentioning
confidence: 77%
“…Finally, some review articles, analyzing alterations in the PI3K/AKT/mTOR pathway in ER+ breast tumors associated with endocrine therapy resistance, where selected. (Olmez et al, 2017).…”
Section: Target Therapy: Cdk 4/6 Inhibitorsmentioning
confidence: 99%
“…Meclizine and flunarizine were more toxic than rapamycin ( Figure 3). Rapamycin has been used in multiple GBM clinical trials (21)(22)(23)(24).…”
Section: Piperazine Drugs Kill Gbmscsmentioning
confidence: 99%
“…Flunarizine reduced GBMSC viability to a similar extent ( Fig.4). Both meclizine and flunarizine were significantly more toxic to GBMSCs than rapamycin, a drug that has been used in several GBM clinical trials (21)(22)(23)(24). The IC50's for meclizine, flunarizine, and rapamycin are 5.3µM, 6.8µM, and 14µM respectively.…”
Section: Comparison Of Gbm Cell Viability After Treatment With Meclizmentioning
confidence: 99%